2009
DOI: 10.1530/rep-08-0442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose mifepristone administration on day 2 after ovulation on transcript profiles in implantation-stage endometrium of rhesus monkeys

Abstract: Progesterone is essential for endometrial receptivity in primates. In studies previously performed using global gene profiling based on microarray technology, attempts have been made to identify changes in gene expression between early luteal-phase and mid-luteal-phase endometria. However, the issue of the putative impact of preimplantation embryo-derived signal in the process of endometrial receptivity was missing in the previous studies. In the present study, an attempt has been made to delineate the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…The results of the RNA-Seq analysis in the present study found that proline dehydrogenase 1 ( PRODH ) was down-regulated and thrombospondin 1 ( THBS1 ) was up-regulated following RU486 administration, and these results are consistent with those described for the human endometrium [64]. In addition, the genes, follistatine-like 1 ( FSTL1 ) and epidermal growth factor receptor ( ERBB3 ), showed similar levels of down-regulation after 12 h of treatment with RU486, and these results are consistent with those previously reported for rhesus monkeys in response to treatment with RU486 for four days [65]. Previous studies have also shown that treatment with RU486 in the early luteal phase inhibits normal down-regulation of the PR gene ( PGR ) [66].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the RNA-Seq analysis in the present study found that proline dehydrogenase 1 ( PRODH ) was down-regulated and thrombospondin 1 ( THBS1 ) was up-regulated following RU486 administration, and these results are consistent with those described for the human endometrium [64]. In addition, the genes, follistatine-like 1 ( FSTL1 ) and epidermal growth factor receptor ( ERBB3 ), showed similar levels of down-regulation after 12 h of treatment with RU486, and these results are consistent with those previously reported for rhesus monkeys in response to treatment with RU486 for four days [65]. Previous studies have also shown that treatment with RU486 in the early luteal phase inhibits normal down-regulation of the PR gene ( PGR ) [66].…”
Section: Discussionsupporting
confidence: 91%
“…The methodological details of RNA extraction followed by the estimation of its yield and purity using standard electrophoretic and spectrophometric protocols and its RIN score using the Agilent 2100 Bioanalyzer, RNA 6000 Nano LabChip kit and Agilent 2100 Expert Software (Agilent Technologies, Santa Clara, CA, USA) have been given elsewhere [8,13]. Individual RNA samples from eutopic and ectopic tissue samples (n = 18) from confirmed stages 3 (n = 8) and 4 (n = 10) collected during proliferative (n = 13) and secretory (n = 5) phases and having RIN scores >8.0 were subjected to whole transcriptome array experiment using the Agilent Whole Human Genome 60-mer 4X44K microarray according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…The methodological details of RNA extraction have been given elsewhere (Ghosh et al 2009). Briefly, total RNA was extracted using TRIzol (Invitrogen) and cleaned up with DNase I (Sigma Chemical Co.) and subjected to re-extraction when it was necessary.…”
Section: Rna Extractionmentioning
confidence: 99%